ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN CRUDE PALM OIL (CPO) EXPORTS IN THE GLOBAL MARKET - Aini Ginting; Suhela Putri Nasution (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
Palm oil stands as a vital commodity within Indonesia’s plantation industry, holding strategic importance and contributing significantly to the country’s foreign exchange earnings primarily through its derivative, Crude Palm Oil (CPO), which is obtained from oil palm fruit. Indonesia currently leads as the world’s top exporter of CPO. Despite this prominent position, the country has yet to develop the capacity to influence or determine global CPO pricing. In fact, 2024 saw a drop in both the volume and value of CPO exports, highlighting persistent challenges in maintaining competitiveness on the international stage. This research seeks to evaluate the extent to which GDP, trade costs, and exchange rates impact Indonesia’s CPO trade value in global markets. The study relies on secondary data sourced from various official and credible institutions, including publications from government bodies and relevant international organizations. A panel data regression model is employed, using the Gravity model approach, as it is well-suited for examining cross- country and time-series data. Findings from the analysis reveal that Indonesia’s per capita GDP, the per capita GDP of importing countries, and exchange rates have a significant effect on the export value of CPO. Conversely, the trade cost variable does not demonstrate a statistically significant impact.